Detection and characterization of an emerging type of Babesia sp. similar to Babesia motasi for the first case of human babesiosis and ticks in Korea - Sung-Hee Hong; Seong-Yoon Kim; Bong Goo Song; Jong Yul Roh; Chong Rae Cho; Chul-Nam Kim; Tae-Hyun Um; Yee Gyung Kwak; Shin-Hyeong Cho; Sang-Eun Lee (Emerging Microbes and Infections)
Babesiosis is a tick-transmitted intraerythrocytic zoonosis. In Korea, the first mortalities were reported in 2005 due to Babesia sp. detection in sheep; herein we report epidemiological and genetic characteristics of a second case of babesiosis. Microscopic analysis of patient blood revealed polymorphic merozoites. To detect Babesia spp., PCR was performed using Babesia specific primers for β-tubulin, 18S rDNA, COB, and COX3 gene fragments. 18S rDNA analysis for Babesia sp., showed 98% homology with ovine Babesia sp. and with Babesia infections in Korea in 2005. Moreover, phylogenetic analysis of 18S rDNA, COB, and COX3 revealed close associations with B. motasi. For identifying the infectious agent, Haemaphysalis longicornis (296) and Haemaphysalis flava (301) were collected around the previous residence of the babesiosis patient. Babesia genes were identified in three H. longicornis: one sample was identified as B. microti and two samples were 98% homologous to B. motasi. Our study is the first direct confirmation of the infectious agent for human babesiosis. This case most likely resulted from tick bites from ticks near the patient house of the babesiosis patient. H. longicornis has been implicated as a vector of B. microti and other Babesia sp. infections.